Selective Catalytic Reduction of NOx by CO over Cu(Fe)/SBA-15 Catalysts: Effects of the Metal Loading on the Catalytic Activity - Souza, Monique S.; Martins, Antonio J.; Ribeiro, Jackson Anderson S.; Campos, Adriana; Oliveira, Alcineia C.; Jucá, Raí F.; Saraiva, Gilberto D.; Rodríguez-Castellón, Enrique; Araujo, Rinaldo S. (IOAP-MDPI, 2023)
Mesoporous Cu(Fe)/SBA-15 catalysts were prepared with distinct metal loadings of ca. 2–10 wt.%. A detailed set of characterizations using X-ray diffraction (XRD), electron paramagnetic resonance (EPR), transmission electron microscopy (TEM), scanning electron microscopy coupled to energy dispersive spectroscopy (SEM-EDS), Mössbauer spectroscopy, X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy was performed to correlate the relationship among structure, electronic properties and catalytic performances. All solids were evaluated in the selective catalytic reduction of NOx in the presence of CO (CO-SCR). The influence of the metal loadings on the overall activity indicated that introducing high amounts of Fe or Cu on the catalysts was beneficial to form either CuO or α-Fe2O3 clusters. Cux/SBA-15 series exhibited more efficient activity and poison-tolerant ability during CO-SCR reaction, in contrast to Fex/SBA-15. In spite of the Fe species introduced on SBA-15 having structural features similar to those of Cu ones, low interactions among Fe nanoparticles, silica and clusters impeded the high performances of Fe10/SBA-15. XPS revealed the Fe species in a more oxidized state, indicating the stability of the solid after the catalytic tests, in agreement with EPR and Raman spectroscopy. Cu8/SBA-15 worked better, being recyclable due to the interaction of the Cu2+ ions with SBA-15, avoiding the deactivation of the catalyst.
Keywords: Química inorgánica; SCR-CO; Cu; Fe; Metal loadings; CuO clusters